As asas da mudança : incertezas e desafios de uma professora em uma sala digital de língua inglesa - Lima, Ana Paola de Souza (2013)
Considering the recent spread of digital classrooms, computer-mediated education and other technologies which accompany such innovations, the teachers’ theoretical and technical training becomes an urgent action to be put into practice, in order to contribute to relevant and productive learning in the global world, as well as the transformation of educators in order to promote reflexive-critical process to minimize the inequalities and injustices reproduced inside schools and classrooms. Thus, this study is inserted in the context of long distance education and had as aim to perceive the level of understanding of the participant teachers concerning the processes of Critical Literacy and Multiliteracies, and also my own process of appropriation of the theories which guided this study, related to my educational practice. The discourse community of this study was composed by English teachers from public and private schools, and idioms centers, from different Brazilian states. I analyzed the posts and comments which emerged in the course Reflexive-Critical Formation of English Teachers, which took place in the virtual environment Moodle, in an attempt to find evidence of understanding of those teachers considering the aforementioned theories. The study received theoretical support from Menezes de Souza & Monte-Mór (2006), Assis-Peterson (2010), Brydon (2011), Magnani (2007), Menezes de Souza (2011), Paiva (2013), Cope & Kalantzis (2000), Kalantzis & Cope (2011), concerning the critical formation by means of language. The theoretical and methodological course was the interpretativism research, of ethnographic nature, with the support of King & Horrocks (2010), Bortoni-Ricardo (2008), and Denzin & Lincoln (2006). The results suggest evidences that point to the occurrence of reflexive- critical processes, based on the adopted theories, in different levels of complexity, contributing to the continuing training of those language teachers observed.